Improvement of methods of creating hybrids of cabbage - Anna I. Mineykina; Lyudmila L. Bondareva; Darya V. Shumilina; Elena A. Domblides; Alexey V. Soldatenko (Овощи России, 2019)
Relevance One of the basic directions of the cabbage crop breeding is the creation of F1 hybrids with a complex of economically valuable traits. This process is difficult and time-consuming as to get pure lines must be within 6-12 years hold inbreeding. Herewith not every line gives the desired heterotic effect that also requires additional verification. Methods Biotechnological method culture of isolated microspores in vitro, which allows in the first generation to receive a line with 100% homozygosity, was used to speed up the breeding process. Combination ability were performed in complete diallel cross on the basic morphological signs. Results Culture medium for cultivation of isolated microspores in vitro was optimized for each genotype of cabbage for the best embryoids regeneration. Maximum amount of embryoids was received on medium with pH 6.2 using ampicillin 100 mg/l and zeatin 1 mg/l: 466.7 ± 153.2 PCs/100 buds. A new source material for breeding – doubled haploid lines of cabbage was received. Lines – the best parents for F1 hybrids with high yield, compact rosette of leaves, with optimum inside and short outside cabbage stump was created. Studies have shown that optimization of breeding process in case of creation of pure lines of cabbage in 3 years with microspore culture requires to reduce the breeding process in 2 times.